Effectiveness of Settlement of Bad Credit Through Memo Decision on Credit Settlement and Auction at PT Bank BTPN Tbk, Cakranegara Branch (International Journal of Scientific Research and Management (IJSRM), 2019)
This study aims to determine the criteria of bad credit that can be submitted to the settlement through the Credit Settlement Decision Memorandum (MKPK), and Auction at PT. Bank BTPN Tbk, Cakranegara Branch, as well as procedures and obstacles, along with their implementation in the field. This research uses 2 (two) theories, namely effectiveness theory and dispute resolution theory. This research is empirical normative research. Data collection is obtained from the results of interviews, and observations. The conclusion of the results of this study are 1. Settlement of bad loans that can be done with MKPK and auctions are: a. Guaranteed secured features; b. Arrears up to> 180 days; c. Has been issued a warning letter 1-3 (SP1-SP3); d. Has been restructured. 2. The filing procedure for MKPK and auction is almost the same between the two, the difference is for MKPK the initiative to propose the arrival of the debtor, by attaching a request letter from the debtor, while the auction initiative comes from the creditor/bank. 3. Implementation of MKPK and auction at Cakranegara Branch BTPN, more dominantly conducted by auction, 61.70% auction bidding ratio of total bad loans, with the ratio successfully executed as much as 6.89%. Whereas the settlement with MKPK either with MKPK partially or with MKPK at once, submission of 38.29% with a success ratio of 66.66%.